Compliance of microcredit authority rules, 2010: a study on selected NGOs - Rahman, Mohammad Moshiur (BRAC University, 2014)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2013.